The 1930s Generation’s Conformism and Illusions - Mitaitė, Donata (Colloquia, 2016)
The author of this article draws on memoirs, archival material, and published texts to analyse the situation and work of three poets of the 1930s generation (Algimantas Baltakis, Alfonsas Maldonis, and Justinas Marcinkevičius), from their debuts to 1968. Rather than fight a system whose essence they had grasped and feared, these poets consciously chose to live and work within Soviet society. Archival texts indicate that they did not believe in the positive changes Soviet life promised; they only celebrated these in their published poems. Signs of conformism diminished during the years of the so-called “thaw,” when ideological pressure began to lighten. Among other things, their works from that period seem to recall the nation’s period of rebirth at the end of the nineteenth century. They wrote about a spring which marked change not only in nature, but in society; they spoke about decreasing fear; they mocked the dogmatists. But like a large portion of Soviet society, these poets did not believe that a fundamental change of system was possible; rather, they looked hopefully to the example of Czechoslovakia and its efforts to at least reform socialism, to give it a “human face,” and in their poetry, they created a portrait of Lenin as an ideal, humane leader. Their illusions were crushed in 1968, their disillusionment recorded in their poetry